Needs Analysis for Developing A Thinking-Based Learning Module In Mathematics Learning - et. al., Ruslina Othman , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
It is widely recognized that the application of thinking skills in the teaching and learning of Mathematics has become an important need in the Malaysian context. The level of mathematics teachers understanding on the importance of thinking skills is, therefore, a matter of concern. This need analysis study aims to identify the extent to which thinking skills training has been accepted by Malaysian mathematics teachers and to identify the topics in Form One Mathematics which requires thinking skills infusion. This study used an online questionnaire (Google Forms) of Need Analysis Survey involving 52 respondents among mathematics teachers nationwide. Data are analysed using the descriptive statistics. The finding of the study revealed that although almost ¾ of them have attended Higher Order Thinking skills (HOTS) courses, yet half of them are still unclear about conducting HOTS teaching. Furthermore, they are not provided with a module to guide HOTS in teaching. This study also found that the topic of Algebraic Expression achieved the highest score as the topic of choice for teachers, which indicated that TS should be infused in this topic during the development of the module. It was concluded that there is a need to develop a thinking-based learning module for Algebraic Expression topic which would enhance the quality of thinking among students in order to enable them to compete globally.